Clinical application of VATS combined with 3D-CTBA in anatomical basal segmentectomy - Zhang, Lening; Wang, Tuhui; Feng, Yonggang; Chen, Yizhao; Feng, Chong; Qin, Dongliang; Han, Chunshan (Frontiers in Oncology, 2023)
Objective: To summarize the clinical application experience of VATS combined with 3D-CTBA in anatomical basal segmentectomy. Methods: The clinical data of 42 patients who underwent bilateral lower basal segmentectomy by video-assisted thoracic surgery (VATS) combined with three-dimensional computed tomography-bronchography and angiography (3D-CTBA) in our hospital from January 2020 to June 2022 were retrospectively analyzed, including 20 males and 22 females, with a median age of 48 (30-65) years. The incision selection was as follows: an incision of approximately 1cm in the 7th intercostal space of the midaxillary line was used as the observation port, an incision of approximately 2-3cm in the 4th or 5th intercostal space of anterior axillary line (add or not an incision of approximately 1cm in the 9th intercostal space of posterior axillary line) was used as the operation ports (multiportal VATS); An incision of approximately 4cm in the fifth intercostal space of the anterior axillary line was made as operation port (uniportal VATS). Combined with preoperative enhanced CT and 3D-CTBA technology, the abnormal bronchus, arteries and veins were identified during operation. Results: All the operations were successfully completed without conversion to thoracotomy or lobectomy. The median operation time was 125（90-176）min, the median intraoperative blood loss was 15 (10-50) mL, the median postoperative drainage time was 3 (2-17) d, the postoperative hospital stay was 5(3-20) d. . The median number of resected lymph nodes was 6 (5-8). There was no in-hospital death. Postoperative pulmonary infection occurred in 1 case, venous thrombosis in both lower limbs in 3 cases, pulmonary embolism in 1 case, and persistent air leakage from the drainage tube in 5 cases, all of which were improved by conservative treatment. Two cases of pleural effusion after discharge were improved after ultrasound guided drainage. Postoperative pathology showed 31 cases of minimally invasive adenocarcinoma, 6 cases of adenocarcinoma in-situ, 3 cases of severe atypical hyperplasia, and 2 cases of other benign nodules. All cases were negative for lymph nodes. Conclusion: VATS combined with 3D-CTBA is safe and feasible in anatomical basal segmentectomy.